Development of Ceramic Materials and Application of Novel Physical Analysis Methods to Enhance Solid Oxide Fuel Cells and Solid Oxide Electrolysis Cells. (30th May 2017) - Lust, Enn; Lillmaa, Kadi; Nurk, Gunnar; Kanarbik, Rait; Möller, Priit; Kivi, Indrek; Vestli, Mihkel; Maide, Martin; Korjus, Ove; Salvan, Laur Kristjan; Kukk, Freddy
Abstract : Different physical (FIB-TOF-SIMS, SXAS, XRD, high-temperature XRD under electrochemical working conditions, FIB-SEM-EDX, AFM, gas chromatography-mass spectrometry, BET) and electrochemical (cyclic voltammetry, chronoamperometry and electrochemical impedance) methods have been applied for detailed analysis of solid oxide fuel cell materials. Solid oxide fuel and co-electrolysis cell single cells based on Ni-free anodes/cathodes as well as Ni-Ce0.9 Gd0.1 O2- d or Ni-Zr0.92 Y0.08 O2- d supporting anodes/cathodes, bi-layered Zr0.92 Y0.08 O2- d | Ce0.9 Gd0.1 O2- d or Zr0.94 Sc0.06 O2- d | Ce0.9 Gd0.1 O2- d electrolytes and micro-meso-porous La0.6 Sr0.4 CoO3- d, Gd0.6 Sr0.4 CoO3- d, La0.6 Sr0.4 Co0.8 Fe0.2 O3- d or Pr0.6 Sr0.4 CoO3- d cathodes/anodes, respectively. For preparation of electrodes and electrolytes various nano-microporous powders, different sintering temperatures and pore former additions in the raw cathode and anode pastes have been applied. Ni-free anodes/cathodes have been synthesized using the impregnation method and tested at temperatures from 650 to 800 °C. Influence of the electrodes porosity, chemical composition and also of the bi-layered electrolyte properties on the power density of the SOFC and SOEC single cells has been established and analyzed. The synchrotron radiation based X-ray absorption spectroscopy under electrochemical polarization and different fuel feeding (pressure, gas flow rate, etc.), chemical composition (H2 S and other sulphur containing compounds, halides, etc.) and temperature cycling conditions has been applied for chemical analysis of surface composition of the SOFC anodes.